2023
DOI: 10.29133/yyutbd.1251495
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Secondary Metabolites in Different Part of the Butterfly Pea (Clitoria ternatea) Plant with Antioxidant Activity

Waras NURCHOLİS,
Tenku Muhammad IQBAL,
Sulistiyani SULISTIYANI
et al.

Abstract: The butterfly pea flower (Clitoria ternatea) is widely used in traditional medicine and has the potential to be an antioxidant. The study aimed to compare the antioxidant capacity of the ethanol extract of the butterfly pea flower and the metabolite profile of the n-hexane fraction in different parts of the plant. The butterfly pea flower was planted for 12 weeks, and as many as 30 plants were in the Tropical Biopharmaca Research Center Cikabayan experimental garden, Bogor, Indonesia. Plant measurements includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The current study indicated that the CTE-containing supplement may be safe and support gut health. A healthy gut includes multiple positive aspects of the gastrointestinal tract, specifically effective digestive and absorption functions of the intestinal brush border and villi improvement with phenolic and flavonoids, especially anthocyanin [ 29 ], found in flowers (4.72 mg/L) and leaves (2.92 mg/L) [ 30 ]. The phenolic content was found in flowers and leaves with values of 37.58 and 56.74 GAE/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study indicated that the CTE-containing supplement may be safe and support gut health. A healthy gut includes multiple positive aspects of the gastrointestinal tract, specifically effective digestive and absorption functions of the intestinal brush border and villi improvement with phenolic and flavonoids, especially anthocyanin [ 29 ], found in flowers (4.72 mg/L) and leaves (2.92 mg/L) [ 30 ]. The phenolic content was found in flowers and leaves with values of 37.58 and 56.74 GAE/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic content was found in flowers and leaves with values of 37.58 and 56.74 GAE/g, respectively. The leaves had the greatest total flavonoid content (5.69 mg QE/g), while the lowest level of flavonoids was found in the flowers (1.45 mg QE/g) [ 30 ]. These secondary metabolites are compounds in specific cells that are indirectly essential for respiratory photosynthesis or the metabolism and survival of plants, as they protect plant tissues from injuries and insect and animal attacks.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, people are beginning to recognize the potential of medicinal herbs in curing ailments with few side effects. For people who are aware that long-term use of pharmaceutical medications may have serious adverse effects, medicinal plants are a great therapeutic choice (Putra and Rifa'i, 2019;Putra et al, 2021;Rahayu et al, 2022;Nurcholis et al, 2023). In developing nations, traditional medicine is the primary therapy for around 80% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…For effective integration of butterfly flower leaves in wound healing for postpartum women, it is essential to ascertain the content of secondary metabolites through phytochemical screening tests(Asma`a Mohsen Al-Wajih et al, 2022;Hanafiah et al, 2017;Nurcholi̇S et al, 2023). Identifying the specific compounds and their levels is crucial for understanding their role in the observed pharmacological activities (Omar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%